Dynamic factor demand in a rationing model - Werner Smolny (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1992)
A dynamic model of the firm is worked out, which pays special attention to a delayed adjustment of employment, investment, and the production technology. A three-step decision structure is assumed, with short-run adjustment of output, medium-run adjustment of employment, and long-run adjustment of the capital stock and capital-labour substitution. Special attention is paid to dynamic inefficiencies like underutilizations of the capital stock and labour hoarding. Market disequilibrium is introduced by allowing for a sluggish adjustment of wages and prices. The model of the firm is complemented by explicit aggregation over firms. The aggregate model is estimated for the FRG.
Keywords: 330; Disequilibrium; macroeconomic model; aggregation; micro market; dynamic labour demand; investment; rationing model